If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(r + -6) = -37 Reorder the terms: -2(-6 + r) = -37 (-6 * -2 + r * -2) = -37 (12 + -2r) = -37 Solving 12 + -2r = -37 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -2r = -37 + -12 Combine like terms: 12 + -12 = 0 0 + -2r = -37 + -12 -2r = -37 + -12 Combine like terms: -37 + -12 = -49 -2r = -49 Divide each side by '-2'. r = 24.5 Simplifying r = 24.5
| 2*x+7=5 | | (y-15)-(1y-10)=19 | | 3(2x-5)-4(x-1)=(-3x-6)-3(x+3) | | 5*x+3=13 | | -9x-24=-11x+10 | | -6t=-39 | | log(x+15)-log(x)=0.65 | | 40x=18000+5y | | -47-91=156-9x | | -32-4x=46-x | | 2x-5=5-2 | | 5x-3(2x-10)=25 | | 34+03*2-25+5= | | z^2-(3+4i)z-1-5i=0 | | -46-(-28)= | | 78+n=3n-40 | | 5y-8=12x+4 | | 5y+24=y-8 | | 1.84g-8=0.28 | | 48=3.2x | | 4x+8-8x=32-4x | | 84+n=36-3n | | 3y-18=6 | | 7-1.5x=62.5 | | 4x-47=7x+22 | | 5+5+5+5+5=555 | | 7-1.5x=64 | | 4x-2x=7+13 | | 4a+3=3a+13 | | -6a+(-18)= | | 180=2X+5+3X-5 | | 2x+x+12.5=116 |